Tipologi Wisata Gastronomi di Kabupaten Gianyar: Implementasi Triangle Gastronomi Indonesia - Aryanti, Ni Nyoman Sri; Harmayani, Eni; Udasmoro, Wening; Mutiarin, Dyah (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
This study examines the typology of gastronomic tourism in Gianyar Regency, Bali, within the framework of the Triangle Concept of Indonesian Gastronomy (food, culture, and history). A qualitative approach was employed through semi-structured interviews, participatory observation, and documentation of gastronomic practices in Ubud and its surroundings. The findings identify four main typologies: observational culinary tourism, emphasizing aesthetic and sensory experiences; participatory culinary tourism, particularly cooking classes that transform domestic space into cultural learning arenas; agro-gastronomy, which integrates farming, local food production, and eco-tourism; and food festivals, functioning as platforms for cultural representation, entrepreneurship, and international collaboration. These typologies demonstrate how gastronomy in Gianyar is not merely a culinary attraction but also a vehicle for cultural preservation, social transformation, and sustainable community-based tourism. By highlighting the synergy of food, culture, and history, this study contributes to a deeper understanding of gastronomic tourism as both a symbolic and economic driver in Bali’s destination development.